PRE-NUCLEATION MECHANISMS OF FLAT PERYLENE-BASED ORGANIC NANOCRYSTALS - Husanova, Dilfuza; Ochilov, Jurat; Yusupov, Maksudbek; Khalilov, Umedjon (MMIT Proceedings, 2023)
Although perylene-based organic nanocrystals are used in various fields, understanding their pre-nucleation processes (considered the first steps of the synthesis) is still elusive. In this work, the nature of pre-nucleation processes of organic crystal synthesis based on two types of flat perylene molecules is studied using reactive molecular dynamics simulations. The obtained results indicate that the additional methoxy group significantly affects the clustering rate of molecules and the structure of the formed clusters. In addition, the cluster formation behavior for both molecules is explained by Ostwald ripening theory. The analysis, which is based on the Gibbs free energy of formation, clarifies that this phenomenon depends on the volume-dependent stability of clusters. In general, this study contributes to a better understanding of the onset of synthesis of organic nanocrystals based on flat perylene molecules for modern nanotechnology